Pseudognaphalium fastigiatum (Compositae: Gnaphalieae) es el nombre correcto para P. cabrerae - Bayón, Néstor David (2013)
Pseudognaphalium cabrerae (S. E. Freire) Deble was proposed as a new combination in 2006 for the South American Gnaphalium fastigiatum Philippi (1895), non Thunb. (1800), nec Schrank (1824), also called G. philippii Cabrera (1941), non Gand. (1918). However, P. cabrerae is invalid under ICBN rules. Pseudognaphalium fastigiatum is proposed as the correct name for this taxon.